Adrenaline Rush - Mohd Daud, Muhammad Nur Firdaus; Entawin, Affy Jackleyinda; Edip, Jannette; Balakan, Marcella Rosabell (2012)
In the relentless transform and life in the fast lane that is now happening in Malaysia, the necessity for higher achievement and everything-more situation including the need for better entertainment needs to be fulfilled. That is why we choose to be involved in the entertainment and sport industry providing the best Go-kart experience to fulfill the high demand of extreme sports for entertainment. Go-kart is the most exciting and exhilarating activity that anyone could wish to take part in. The name Go-kart is actually known as Super kart. A Go-kart is an open wheeled vehicle which comes in a variety of forms, from motorless models to high-performance go-karts which are made for racing. Unlike a normal car, it is much smaller in size which could only fit one or two people and the driver have to sit very close to the ground. Other than that, there are no front, back, side wall and roof to protect you from the weather. Thus, making it a very challenging sport. Moreover, the concept of the go-karts that will be used in the business are eco-friendly karts with zero emission of carbon to support the 'Go-kart, Go green' campaign to save the environment. The go karts used are fully battery powered and are rechargeable with no usage of fuel. We form the business of 5 partners; Muhammad Nur Firdaus b. Mohd Daud, Affy Jackleyinda Entawin, Jannette Edip, Marcella Rosabell and Amirah Mahirah Askar; and targeting customer from all range of ages because our business can fit to serve their need of sports entertainment. This is why we choose go-kart because we see it as a sustainable and profitable market in Malaysia particularly in Kota Kinabalu because there are no competitors except for the nearest in Sandakan. The success of the business in future is hoped for and to be recognize globally as a leading eco-friendly karting facility. We strive to be the best in the industry and also to serve the people better.